2012
DOI: 10.1371/journal.pone.0042463
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Clinical Characterization of the Variable Phenotype in Korean Families with Hearing Loss Associated with the Mitochondrial A1555G Mutation

Abstract: Hearing loss, which is genetically heterogeneous, can be caused by mutations in the mitochondrial DNA (mtDNA). The A1555G mutation of the 12S ribosomal RNA (rRNA) gene in the mtDNA has been associated with both aminoglycoside-induced and non-syndromic hearing loss in many ethnic populations. Here, we report for the first time the clinical and genetic characterization of nine Korean pedigrees with aminoglycoside-induced and non-syndromic hearing loss. These Korean families carry in the A1555G mutation of 12S rR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
5
22
0
Order By: Relevance
“…Based on previous genetic studies of HL in the Korean population, we selected the seven most common mutations that lead to hereditary HL [8][12], [31]. Multiplex genotyping of these seven mutations was successfully performed using SNaPshot minisequencing, which produced accurate data and a detection rate of the mutations that was found to account for up to 40% of the causative mutant alleles associated with prelingual HL in Koreans [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on previous genetic studies of HL in the Korean population, we selected the seven most common mutations that lead to hereditary HL [8][12], [31]. Multiplex genotyping of these seven mutations was successfully performed using SNaPshot minisequencing, which produced accurate data and a detection rate of the mutations that was found to account for up to 40% of the causative mutant alleles associated with prelingual HL in Koreans [8].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial DNA mutations have also been reported in both nonsyndromic and syndromic HL. Among these mutations, only the m.1555A>G mutation of the MT-RNR1 gene (OMIM 561000) has been identified repeatedly in Koreans with HL by our previous studies [11], [12]. Based on the prevalence of mutations from the previous studies, we selected 7 mutations which show the high frequencies in Korean hearing loss population and designed the method to detect effectively mutant alleles through rapid screening: c.235delC of GJB2 , c.919-2A>G and c.2168A>G of SLC26A4 and m.1555A>G of the MT-RNR1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…The primers for both genes were the same as previously reported (Bae et al, 2012). Amplified DNA fragments were purified with a gel extraction kit (Qiagen) and then sequenced by the ABI 377 sequencer.…”
Section: Sanger Sequencingmentioning
confidence: 99%
“…Of the mutations in human mtDNA, A1555G is one of the most common pathogenic mutations associated with aminoglycoside ototoxicity (6). However, increasing evidence has shown that the A1555G mutation cannot directly lead to hearing loss, as among pedigrees with maternally inherited deafness, a certain number of members (despite carrying the A1555G mutation) exhibit different levels of hearing, ranging from normal to profound hearing loss (7)(8)(9)(10)(11). Therefore, aminoglycosides, nuclear-encoded genes and the mtDNA genetic background may actively function in the occurrence of deafness (12,13).…”
Section: Introductionmentioning
confidence: 99%